EFEKTIVITAS MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DALAM MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 1 POLEWALI KABUPATEN POLEWALI MANDAR - Andriani Andriani (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2014)
This study aimed to: (1) assess the effectiveness of problem-based learning model in writing exposition text at class X SMA Negeri 1 Polewali; (2) assess the effectiveness of conventional teaching in writing exposition text at class X SMA Negeri 1 Polewali; and (3) prove a learning model based on effective problem used in writing exposition text at class X SMA Negeri 1 Polewali. This research employed experimental research and the population was the students at class X SMA Negeri 1 Polewali, 148 students were spread out into five classes under Mathematics and Natural Sciences Department (MND), from class X MND1 to class X MND5. The researcher used random sampling technique and took 30 students of class X MND5 as the experimental class and 30 students of class X MND1 as the control class, and test was given as the instrument of this research. In collecting data, the researcher used pre-test, treatment, and post-test. Data obtained in two ways analyzes by descriptive statistics and inferential statistics. The results showed that: first, the skills of class X SMA Negeri 1 Polewali Polewali Mandar in writing exposition text trough conventional teaching showed bad effect where some students reached less than 2, 66.